Effective suicide prevention strategies in primary healthcare settings: a systematic review - Hosein Azizi; Elham Davtalab Esmaeili; Farzad Khodamoradi; Ehsan Sarbazi (Middle East Current Psychiatry, 2022)
Abstract Background There is a fundamental need for health systems, health managers, and policymakers to identify effective components of suicide prevention strategies (SPS) and programs in primary healthcare (PHC) settings. Accordingly, this systematic review aimed to identify and summarize effective and significant evidence on suicide prevention in PHC setting. We systematically searched the published literature in English from PubMed, Web of Science, Scopus, CINAHL, PsychoINFO, and Embase up to 31 July 2022. The study searched all records reporting effective and significant strategies and programs on suicide prevention in PHC settings. A content analysis approach was carried out to extract major components of suicide prevention strategies in PHC settings. Results A total of 10 records (8 original articles and 2 reports) with 1,199,986 samples were included. In all the included articles, SPS decreased suicide rates. The majority of studies were conducted among the general population. The content analysis approach emerged five major components to SPS in PHC setting: (1) training and educating healthcare providers, (2) screening and suicide risk assessment, (3) managing depression symptoms and mental disorders, (4) managing suicide attempters and at-risk cases, and (5) prevention strategies at the general population. Conclusions This review provided reliable evidence for health systems to develop SPS in PHC and practitioners who are eager to provide brief and effective contact interventions for suicide risk to well-serve their patients.